The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/jf203965j
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Composition in the Ripe Fruits of Fragaria Species and Transcriptional Analyses of Key Genes in the Pathway

Abstract: Polyphenolics are important secondary metabolites in strawberry as they fulfill a wide variety of physiological functions and are beneficial to human health. Seventeen structurally well-defined phenolic compounds including phenylpropanoids, flavonols, flavan-3-ols, and anthocyanins were individually analyzed by LC-MS in the ripe fruits of two cultivars of the commercial strawberry (Fragaria × ananassa Duch., Rosaceae) as well as in accessions of F. vesca, F. moschata, and F. chiloensis. Metabolic analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…Strawberries are a source of phenolic compounds such as flavonoids, phenolic acid derivatives, and anthocyanins, which are all synthesized by the phenylpropanoid pathway (Muñoz et al, 2011), in which phenylalanine ammonialyase (PAL) is the key enzyme (Singh et al, 2010). A slight increase in the anthocyanin content in postharvest red fruits treated with ethephon was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strawberries are a source of phenolic compounds such as flavonoids, phenolic acid derivatives, and anthocyanins, which are all synthesized by the phenylpropanoid pathway (Muñoz et al, 2011), in which phenylalanine ammonialyase (PAL) is the key enzyme (Singh et al, 2010). A slight increase in the anthocyanin content in postharvest red fruits treated with ethephon was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, Villarreal et al (2010) observed a significant increase in PAL activity and a decrease in the phenolic content during the ripening of white strawberries treated with ethephon, indicating that a direct correlation is lacking. However, molecular analyzes of the strawberry cultivar Camarosa during ripening led Muñoz et al (2011) to observe higher PAL expression levels in green and red fruit compared to white. These data suggest that differences in the level of anthocyanins and phenolic compounds across stages in the present study may be related to PAL activity.…”
Section: Discussionmentioning
confidence: 99%
“…This minor pigment is responsible for the dark red colors. Pelargonidin-3-rutinoside can also be commonly found in a much smaller proportion in cultivars like "Camarosa" or "Parker," but this molecule is absent from native species like the diploid F. vesca or octoploid F. chiloensis [2,15]. Other anthocyanins have been identified in other cultivars.…”
Section: Types Of Anthocyaninsmentioning
confidence: 99%
“…The same study noted that the fruits showed low levels of CHS, DFR, and F3H, leading to the compelling hypothesis that the allergen was related to pigment synthesis. To test the direct association, Munoz et al (2011) used the agro-infiltration protocol to suppress the allergen in developing fruits [15]. The results show that Fra a suppression leads to decreases in pigmentation, and leads to the speculation that the protein may be required in the transportation of substrates between flavonoid pathway enzymes.…”
Section: Regulation Of Anthocyanin Synthesis In Strawberrymentioning
confidence: 99%
See 1 more Smart Citation